PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN KOMPENSASI FINANSIAL TERHADAP KEPUASAN KERJA PEGAWAI NEGERI SIPIL (PNS) PADA DINAS PEKERJAAN UMUM DAERAH KABUPATEN MOROWALI - Jacub, Muhamad Yusuf (Katalogis, 2016)
The aims of this research are: 1) to determine and analyze the simultaneous influence of transformational leadership, motivation, and financial compensation on civil servants satisfaction in The Office of Public Works in Morowali; 2) to determine and analyze the influence of transformational leadership on civil servants satisfaction in The Office of Public Works in Morowali; 3) to determine and analyze the influence of motivation on civil servants satisfaction in The Office of Public Works in Morowali; 4) to determine and analyze the influence of financial compensation on satisfaction of civil servants in The Office of Public Works in Morowali. The type of this research is explanatory that shows the influence between variables by involving 55 respondents who are selected through census method. Based on multiple linear regressions test, it is concluded that: 1) transformational leadership, motivation, and financial compensation simultaneously influence civil servants satisfaction; 2) transformational leadership positively and significantly influence civil servants satisfaction; 3) motivation positively and significantly influence civil servants satisfaction; 4) financial compensation positively and significantly influence civil servants satisfaction.Â